An agent-based model for collaborative learning to combat antimicrobial resistance: Proof of concept based on broiler production in Senegal - Ndekou, P.P.; Drake, A.; Lomax, J.; Dione, Michel M.; Faye, A.; Nsangou, M.D.N.; Korir, Luke; Sklar, E. (Elsevier, 2023)
Antimicrobial resistance (AMR) is a substantial global One Health problem. This paper reports on initial, proof-of-concept development of an agent-based model (ABM) as part of wider modelling efforts to support collaborations between groups interested in policy development for animal health and food systems. The model simulates AMR in poultry production in Senegal. It simultaneously addresses current policy issues, builds on existing modelling in the domain and describes AMR in the broiler chicken production cycle as seen by producers and veterinarians. This enables implementation and assessment of producer antimicrobial use (AMU) and infection prevention and control (IPC) strategies in terms of immediate economic incentives, potentially helping to advance conversations by addressing national policy priorities. Our model is presented as a flexible tool with promise for extension as part of AMR policy development in Senegal and West Africa, using participatory approaches. This work indicates that ABM can potentially play a useful role in fostering counter-AMR initiatives driven by food system actor behaviour in lower- and middle-income countries (LMIC) more generally.